Heavy Metal Status in Sri Lanka - Rajapaksha, R.W.W.K.A.D.; Tharanya, S.; Senanayake, D.M.J.B.; N.U., Jayawardana (University of Jaffna, 2023)
The growing phenomenon of environmental contamination mainly due to heavy metals have gained considerable attention of both scientific and public communities. Heavy metals are natural constituents of the environment. Indiscriminate human interventions, such as agriculture and related industries have changed the atmospheric geochemical cycles and biochemical balance of heavy metals. It is well established that excess exposure to heavy metals causes adverse effects on both plants and human beings. The present review is based on the current research evidence on the reported levels of toxic heavy metals such as Cadmium (Cd), Lead (Pb), Arsenic (As), Nickel (Ni), Zinc (Zn), Copper (Cu), Mercury (Hg) Manganese (Mn) and Chromium (Cr) in the Sri Lankan geo-environment.
Keywords: Contamination; Geo-environment; Heavy metals; Sri Lanka; Toxic